2014
DOI: 10.1200/jco.2013.51.4265
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Randomized Trial of Weekly Cisplatin and Irradiation Versus Cisplatin and Tirapazamine and Irradiation in Stages IB2, IIA, IIB, IIIB, and IVA Cervical Carcinoma Limited to the Pelvis: A Gynecologic Oncology Group Study

Abstract: A B S T R A C T PurposeThis prospective, randomized phase III intergroup trial of the Gynecologic Oncology Group and National Cancer Institute of Canada Clinical Trials Group was designed to test the effectiveness and safety of adding the hypoxic cell sensitizer tirapazamine (TPZ) to standard cisplatin (CIS) chemoradiotherapy in locally advanced cervix cancer. Patients and MethodsPatients with locally advanced cervix cancer were randomly assigned to CIS chemoradiotherapy versus CIS/TPZ chemoradiotherapy. Prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 31 publications
1
63
2
Order By: Relevance
“…Two head and neck cancer signatures have shown promise as predictive hypoxia biomarkers (12,42,43), illustrating the potential of gene signatures for hypoxia stratification. For cervical cancer, the optimal hypoxia-targeting drug has yet to be defined (7,8), and careful considerations in the study design have to be done due to toxicity problems. Future work should involve multicenter studies for verifying the classifier's prognostic value and testing the predictive impact in a clinical trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two head and neck cancer signatures have shown promise as predictive hypoxia biomarkers (12,42,43), illustrating the potential of gene signatures for hypoxia stratification. For cervical cancer, the optimal hypoxia-targeting drug has yet to be defined (7,8), and careful considerations in the study design have to be done due to toxicity problems. Future work should involve multicenter studies for verifying the classifier's prognostic value and testing the predictive impact in a clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hypoxia is both a potential marker for predicting risk of recurrence and a target in new treatment strategies combined with radiotherapy. Adjuvant hypoxia-modifying treatment has been shown to improve the efficacy of radiotherapy in cervical cancer (6), and combination trials to find the optimal drug have been performed (7,8) and are underway (ClinicalTrials.gov identifier NCT02394652). In many trials, difficulties in detecting drug effects and toxicity are major problems, as patients are randomized to the adjuvant treatment without knowledge of the hypoxia status of the tumor (9).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of over 10,000 patients enrolled in nearly 90 randomized trials over the past 40 years revealed an OR of 0.77 in favor of hypoxia modification strategies (9). Phase III trials have been conducted utilizing radiotherapy with or without (i) increasing oxygen delivery with hyperbaric oxygen (10,11) or carbogen breathing with nicotinamide (12); (ii) the hypoxic cytotoxin, tirapazamine (13,14). Evofosfamide, another hypoxic cytotoxin, was found to yield improved survival in a randomized phase II trial when combined with gemcitabine in patients with pancreatic cancer (15).…”
Section: Introduction and Historical Perspectivementioning
confidence: 99%
“…A satisfactory TPZ/CisPt chemoradiotherapy starting dose was identified. 17 [DiSilvestro 2014] Despite promising results from a phase II trial of combined chemoradiotherapy of head and neck cancers using TPZ combined with CisPt, the phase III trial found no difference in patients (with advanced head and neck cancer not selected for the presence of hypoxia) in overall survival compared to CisPt chemoradiation alone. 18 [Rischin 2010] It is unknown why the phase III trials of DiSilvestro and Rischin failed to reproduce the promising in vitro results or phase II trials of TPZ/CisPt treatments.…”
Section: Introductionmentioning
confidence: 99%